Quasi-biennial oscillation and summer southwest monsoon - RAO , K. S. RAJA; LAKHOLE, N. J. (MAUSAM, 1978)
Stratospheric circulation in the height range of 16 to 60 km in the equatorial region, has been studied using the rocket wind data of Thumba. It is inferred that the quasi-biennial oscillation in the lower and middle stratosphere are out of, phase by six months. The dominant feature in the lower stratosphere is the appearance of the monsoon easterlies during the period June to September. The westerlies or easterlies in the lower stratosphere over the equator extend to about 10°N in the period November to May. In the middle stratosphere, the quasi-biennial oscillation follows a regular alternation of easterlies and westerlies with a downward phase propogation of one km per month, while the quasi-biennial oscillation in the lower stratosphere interacts with the monsoon circulation. The four possible wind phases W, W IE, E and EIW during March to May in the equatorial lower stratosphere are linked with the onset of southwest monsoon near the normal date and normal rains over India. Appearance of the easterlies in the lower stratosphere over Gan Island in May is an indication of the onset of monsoon over Kerala a month later. The Berson westerlies are a poleward extension of the equatorial westerlies, rather than a descent from the upper stratosphere. The out of phase relationship between QBO in the lower and middle, stratospheres suggests an interaction between the QBO and monsoon circulation. The phase of the QBO, over the equator appears to give a prior indication of the onset of the southwest monsoon over Kerala and also the rainfall in the central parts of the country.